Subretinal exudative deposits in central serous chorioretinopathy. - Ie, D (1993)
The presence of subretinal exudation in a patient with neurosensory detachment of the macula frequently suggests the diagnosis of choroidal neovascularisation. A retrospective chart review of newly diagnosed cases of central serous chorioretinopathy revealed 11 patients, seven men and four non-pregnant women, who had plaques of subretinal exudate, which presumably were fibrin. Each of these patients had a solitary plaque that ranged in size from 300 to 1500 microns in diameter. These patients had no signs or a clinical course suggestive of choroidal neovascularisation. In each case the subretinal plaque was overlying an exuberant leak in the retinal pigment epithelium. The exudate was generally present at the initial examination, and usually showed dissolution before or coincident with the resolution of the neurosensory detachment. After resolution of the central serous chorioretinopathy, patients were left with subtle alterations in the retinal pigment epithelium in the areas of the subretinal plaque. These findings are important for two reasons. Firstly, the presence of subretinal exudation does not necessarily rule out the diagnosis of central serous chorioretinopathy. Secondly, pathophysiological theories of central serous chorioretinopathy must explain how the plaques are deposited behind the retina.